Blockade of Cannabinoid CB1 Receptors in the Dorsal Periaqueductal Gray Unmasks the Antinociceptive Effect of Local Injections of Anandamide in Mice - Mascarenhas, Diego C. [UNESP] (2017)
Divergent results in pain management account for the growing number of studies aiming at elucidating the pharmacology of the endocannabinoid/endovanilloid anandamide (AEA) within several pain-related brain structures. For instance, the stimulation of both Transient Receptor Potential Vanilloid type 1 (TRPV1) and Cannabinoid type 1 (CB1) receptors led to paradoxical effects on nociception. Here, we attempted to propose a clear and reproducible methodology to achieve the antinociceptive effect of exogenous AEA within the dorsal periaqueductal gray (dPAG) of mice exposed to the tail-flick test. Accordingly, male Swiss mice received intra-dPAG injection of AEA (CB1/TRPV1 agonist), capsaicin (TRPV1 agonist), WIN (CB1 agonist), AM251 (CB1 antagonist), and 6-iodonordihydrocapsaicin (6-IODO) (TRPV1 selective antagonist) and their nociceptive response was assessed with the tail-flick test. In order to assess AEA effects on nociception specifically at vanilloid or cannabinoid (CB) substrates into the dPAG, mice underwent an intrinsically inactive dose of AM251 or 6-IODO followed by local AEA injections and were subjected to the same test. While intra-dPAG AEA did not change acute pain, local injections of capsaicin or WIN induced a marked TRPV1-and CB1-dependent antinociceptive effect, respectively. Regarding the role of AEA specifically at CB/vanilloid substrates, while the blockade of TRPV1 did not change the lack of effects of intra-dPAG AEA on nociception, local pre-treatment of AM251, a CB1 antagonist, led to a clear AEA-induced antinociception. It seems that the exogenous AEA-induced antinociception is unmasked when it selectively binds to vanilloid substrates, which might be useful to address acute pain in basic and perhaps clinical trials.